Teaching Computer Science in the Universities in Third World Countries: Challenges - Odili, Julius Beneoluchi; Noraziah, Adzhar; Ambar, Radzi; Abd. Wahab, Mohd Helmy; M. A. I., Fakheraldin (ISRES Publishing, 2018)
That Computer Science is fast becoming the moderating disciples in modern education worldwide is not an overstatement. There is virtually no academic or professional discipline that computer science hasnot influenced in the last threedecades. This paper presents the challenges of teaching Computer Science in tertiary institutions in a third world country. Using the Anchor University Lagos as its locale, the paper investigates the challenges being faced by students and teachers, alike, in the teaching of Computer Science. After a comprehensive survey of different cadre of staff and students, the paper asserts that under-funding, insufficient teacher-training facilities, lack of basic educational technology facilities remains some of the primary barriers to effective and efficient teaching cum learning of Computer Science in many developing countries. To address this situations a number of cost-effective recommendations were made to address this problem. Some of which are the need for adequate budgetary provisions to the teaching and learning of computer Science, need for adequate teacher motivation, improvisation of needed facilities and industry cum improved teacher-training syllabus.